Pentagon Fraud Analysis of Fraud Financial Statement Actions: The Role of Family Ownership as Moderation Variable - Rosaria Abadi; Retna Safriliana; Diana Zuhroh; Grahita Chandrarin; Norman Duma Sitinjak (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Financial statements will function optimally if presented with qualitative elements, including easy-to-understand, reliable, comparable, and relevant. In preventing any acts of misrepresentation of financial statements, it is necessary to encourage the ownership of family shares. The research method uses quantitative analysis using the Moderator Regression Analysis (MRA) model. The results of this study indicate that in the first hypothesis, it is suspected that there is an influence of Pressure on financial statements fraud. From the results of the T-test, it is known that the sig value is smaller than 0.05, which is 0.000. The t-count value is greater than the t-table (5.461>1.661). This study concludes that the pressure variable influences fraud. The variable financial statements of Family Ownership cannot strengthen the impact of Competence on fraudulent financial statements, and the variable family ownership cannot enhance the effect of arrogance on fraudulent financial statements.